2019
DOI: 10.1007/s00268-019-05068-x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Compliance to an Enhanced Recovery Protocol and Outcome After Elective Surgery for Gastric Cancer. Results from a Western Population‐Based Prospective Multicenter Study

Abstract: Background The association between compliance to an enhanced recovery protocol (ERAS) and outcome after surgery for gastric cancer has been poorly investigated, particularly in Western patients. The aim of the study was to evaluate whether the rate of adherence to the ERAS program was correlated with outcome and time of discharge. Methods A prospective, observational, multicenter study was designed to be performed at Italian referral centers for gastric surgery. The protocol was discussed and approved by the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 63 publications
3
36
1
4
Order By: Relevance
“…There was also comparable 30-day readmission rate between groups. Similar to our study, recent population-based prospective multicenter study from Western countries reported that it could be possible to gain a 10% reduction in hospital stay for every 10% increase in ERAS compliance [30]. Correlation between morbidity and ERAS compliance rate was also observed [30].…”
Section: Discussionsupporting
confidence: 89%
“…There was also comparable 30-day readmission rate between groups. Similar to our study, recent population-based prospective multicenter study from Western countries reported that it could be possible to gain a 10% reduction in hospital stay for every 10% increase in ERAS compliance [30]. Correlation between morbidity and ERAS compliance rate was also observed [30].…”
Section: Discussionsupporting
confidence: 89%
“…The ERAS CP completion rate of 77.2% was within our expected range (75.4‐85.4%) and was comparable to the completion rates in previous studies (60.3%‐79.6%) . Therefore, ERAS CP components might be applicable to patients with gastric cancer.…”
Section: Discussionsupporting
confidence: 83%
“…The ERAS CP completion rate of 77.2% was within our expected range (75.4-85.4%) and was comparable to the completion rates in previous studies (60.3%-79.6%). 15,16 Therefore, ERAS CP components might be applicable to patients with gastric cancer. The components of the ERAS CP that differed most from those of our conventional CP were the start of oral feeding on POD 1 and discharge on POD 4.…”
Section: Discussionmentioning
confidence: 99%
“…The PCPh may also engage in quality and performance improvement projects and research focused on evaluating the impact of medication management and stewardship‐related interventions within ERPs . Studies have assessed compliance with an ERP as a key indicator for the benefits of the pathway . The PCPh can play a major role in order set creation and electronic medical record documentation of ERP interventions to aid in standardization, pathway compliance assessment, and actions from data collection.…”
Section: Enhanced Recovery Pathways and The Role Of The Perioperativementioning
confidence: 99%
“…40,41 Studies have assessed compliance with an ERP as a key indicator for the benefits of the pathway. 42,43 The PCPh can play a major role in order set creation and electronic medical record documentation of ERP interventions to aid in standardization, pathway compliance assessment, and actions from data collection.…”
Section: Improving Outcomes Across the Surgical Continuum Of Care: mentioning
confidence: 99%